Exploring English Language Proficiency of High School ESL Learners - Dr. Kabita Kumari; Dr. V. Sudhakar (Voices of Teachers and Teacher Educators, 2025)
In spite of the importance that English maintains for socio-economic mobility and access to academic resources, various studies suggest that the proficiency level of students in English is not satisfactory in spite of English being introduced in most schools as a subject from class one or as a medium of instruction. To assess where students stand in proficiency in English, the present study was conducted with 62 students from class IX of a government-run school in Telangana state of India. The students were administered a proficiency test developed by the CBSE. The findings reveal that most of the students have a moderate level of proficiency. The study also suggests that the gender of the students plays a significant role in language proficiency.